PENGARUH SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENCEGAH DAN PEMADAM KEBAKARAN KOTA MEDAN - Paul Ramon Tarigan; Tunggul Sihombing (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
The Occupational Health and Safety Management System (K3) is a process that is carried out continuously during the agency's activities. However, there are still some problems in the implementation of the OHS managements ystem that affect employee performance. This study aims to determine the effect of the occupational safety and health management system on the performance of employees at the Medan City Fire Prevention and Fighting Service (DP2K) in dealing with fire disasters. The method use disassociative/quantitative. Data collection techniques were carried out by distributing questionnaires and documentation. The data obtained were then analyzed using the Smart PLS (Partial Least Square) software version 3.3.2. The sample of this study was 100 respondents from the Medan City Fire Prevention and Fighting Service. From the results of the study, it can be seen that the reisan effect of the occupational safety and health management system on the performance of employees at the Medan City Fire Prevention and Fighting Service (DP2K). This can be seen from the results of the path analysis test of 0.883 and the results of hypothesis testing the t-statistic value of 47.581 which is greater than the t-table of 1.66.